Using the game Racing Fever as a teaching tool of kinematics (Research, Society and Development, 2019)
This work aims to analyze the electronic game Racing Fever, to identify if there are coherences or inconsistencies in the numerical values referring to the displacement, velocity and time quantities provided by it and to propose the game as a teaching tool of kinematics. To do so, we apply the scalar velocity equation to evaluate if there is an equivalence between the velocities provided by the game and the calculated velocities. Theoretically, the study was based on the ideas of Gee (2003), Coelho and Haguenauer (2004) and Short (2012), among others. With our research, it was possible to conclude that there is no equivalence between the velocity values provided by the game and the calculated velocities, which allowed us to interpret this game as incoherent. In this way, we propose that teachers use the game in the classroom, instigating students to do the same analysis of the game.